Games among cannibals: competition to cannibalize and parent-offspring conflict lead to increased sibling cannibalism. - Perry, J; Roitberg, B (2005)
Sibling cannibalism occurs in many species, yet understanding of sibling cannibalism as an adaptation currently lags behind understanding of other antagonistic interactions among siblings. Observed sibling cannibalism phenotypes likely reflect the interaction between competitive games among siblings and parent-offspring conflict. Using a game-theoretic approach, we derive optimal offspring cannibalism behaviour and parental modifiers that limit or facilitate cannibalism. The results are compared to contemporary frequency-independent analysis. With the addition of game interactions among siblings or parent-offspring co-evolution, our model predicts increased cannibalism (compared to the frequency-independent prediction), as offspring compete to eat siblings. When infertile eggs are present--strengthening competition--offspring risk eating viable siblings in order to gain access to infertile eggs, intensifying parent-offspring conflict. We use the results to make new predictions about the occurrence of sibling cannibalism. Additionally, we demonstrate the utility of trophic egg laying as a maternal mechanism to promote egg eating.